Implications of the Implementation of the Marriage Age Limit After the Enactment of Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage at the Pandan Religious Court - Sri Rahmadani; Henry Aspan; Mhd. Azhali Siregar (International Journal of Society and Law, 2025)
The main problem is the existence of problems that arise after the amendment of Law Number 1 of 1974 concerning marriage at the Pandan Religious Court and the efforts made by the Pandan Religious Court against the emergence of problems after the amendment of Law Number 1 of 1974 concerning marriage. The purpose of this research is to describe and analyze the implications that arise and solutions after the amendment of Law Number 1 of 1974 concerning Marriage at the Pandan Religious Court. This type of research is field research, using a qualitative method with a case study approach. The results of the study show that, the implications that emerged after the amendment of Law number 1 of 1974 concerning marriage at the Pandan Religious Court are the increase in the number of marriage dispensation applications. The solution to the problems that arose after the amendment of Law Number 1 of 1974 concerning marriage at the Pandan Religious Court is to provide advice and a persuasive approach to the child to cancel his intention to marry at an early age, and if this is not considered acceptable to the child, then it is recommended to apply for a marriage dispensation. The results are based on the decision of the Religious Court. The conditions that must be met in filing a marriage dispensation application case at the Religious Court are as follows: 1). Application Letter, 2). Copy of the ID card of the parent/guardian concerned, 3). Copy of the Applicant's Family Card, 4). Copy of the Birth Certificate / ID card of the child, 5). Copy of ID card / birth certificate of the prospective husband/wife, 6). Copy of the child's last Education Diploma and/or certificate of still being in school from the child's school, 7). A copy of the Letter of Rejection from the Sub-district Religious Affairs Office and 8). Paying the cost of the case, the Applicant who cannot afford it can apply for a free marriage dispensation (prodeo)